Recent Trends in Insured and Uninsured Unemployment: Is There an Explanation? - Blank, R. M.; Card, D. E. (Quarterly Journal of Economics, 1991)
This paper explores the recent decline in the fraction of unemployed workers who receive unemployment insurance benefits. Using March Current Population Surveys, we compare the fraction who are potentially eligible for benefits with the fraction who receive them. The decline in insured unemployment is almost entirely due to a decline in the early 1980s in the takeup rate for benefits. We analyze the determinants of the takeup rate, using both aggregated state-level data and micro-data. At least half the decline is due to an increasing share of unemployment in states with lower takeup rates.